Unravelling genetic causality of haematopoiesis on bone metabolism in human. Issue 6 (26th October 2022) - Ho, Shun-Cheong; Li, Gloria Hoi-Yee; Leung, Anskar Yu-Hung; Tan, Kathryn C B; Cheung, Ching-Lung
Abstract : Objective: Haematopoiesis was shown to regulate bone metabolism in in vivo studies. However, whether haematopoiesis has causal effects on bone health has never been investigated in humans. We aimed to evaluate the causal relationships of blood traits with bone mineral density (BMD) and fracture. Design and methods: Using two-sample Mendelian randomization, causal relationship of 29 blood traits with estimated BMD (eBMD), total body BMD (TBBMD), lumbar spine BMD (LSBMD), femoral neck BMD (FNBMD) and fracture were evaluated by inverse-variance weighted (IVW) method and multiple sensitivity analyses. Relevant genetic data were obtained from the largest possible publicly available genome-wide association studies. Results: Eight genetically determined red blood cell traits showed positive causal effects on eBMD, with beta estimates ranging from 0.009 (mean corpuscular haemoglobin) to 0.057 (haemoglobin concentration), while three white blood cell traits, including lymphocyte count (beta: −0.020; 95% CI: −0.033 to −0.007), neutrophil count (beta: −0.020; 95% CI: −0.035 to −0.006) and white blood cell count (beta: −0.027; 95% CI: −0.039 to −0.014), were inversely associated with eBMD. Causal effects for six of these blood traits were validated on TBBMD, LSBMD, FNBMD and/or fracture. The association of reticulocyte count (beta: 0.040; 95% CI: 0.016 to 0.063), haemoglobin (beta: 0.058; 95% CI: 0.021 to 0.094) and mean corpuscular haemoglobin concentration (beta: 0.030; 95% CI: 0.007 to 0.054) with eBMD remained significant in multivariable IVW analyses adjusted for other blood traits. Conclusion: This study provided evidence that haematopoietic system might regulate the skeletal system in humans and suggested the possible pathophysiology of bone diseases among people with haematological diseases. Significance statement: We conducted a novel Mendelian randomization study investigating the causal relationship of blood cells with bone mineral density. Red and white blood cell traits have positive and inverse causal relationship with bone mineral density, respectively, suggesting a potential link of haematopoietic system with the skeletal system in humans. Current findings suggest individuals with related haematological diseases, such as anaemia and leukocytosis, may have a lifelong increased risk of osteoporosis and/or fracture. Given that complete blood count is commonly performed in clinical setting, whether complete blood count can be used to predict fracture risk warrants further investigation.